Accuracy of computer‐guided implantation in a human cadaver model. Issue 10 (15th September 2014) - Yatzkair, Gustavo; Cheng, Alice; Brodie, Stan; Raviv, Eli; Boyan, Barbara D.; Schwartz, Zvi
Abstract Objectives To examine the accuracy of computer‐guided implantation using a human cadaver model with reduced experimental variability. Materials and methods Twenty‐eight (28) dental implants representing 12 clinical cases were placed in four cadaver heads using a static guided implantation template. All planning and surgeries were performed by one clinician. All radiographs and measurements were performed by two examiners. The distance of the implants from buccal and lingual bone and mesial implant or tooth was analyzed at the apical and coronal levels, and measurements were compared to the planned values. Results No significant differences were seen between planned and implanted measurements. Average deviation of an implant from its planning radiograph was 0.8 mm, which is within the range of variability expected from CT analysis. Conclusions Guided implantation can be used safely with a margin of error of 1 mm.